GLOBAL WARMING, THE ISSUES IT DRIVES, AND THE POLICY ACTIONS REQUIRED IN RESPONSE - Kayumov Abdulatif Abdumalikovich (American Journals Publishing, 2025)
Global warming in the world, its impact on the world's population, the melting of glaciers and rising sea levels as a result of climate change, flooding of regions, population migration, and the uncontrolled release of greenhouse gas emissions into the atmosphere are covered in this article. Keywords: Climate change, global warming, glaciers, greenhouse gases, melting glaciers, sea level rise, renewable energy.
Keywords: Climate change, global warming, glaciers, greenhouse gases, melting glaciers, sea level rise, renewable energy sources.